Might High-Intensity Interval Exercise Be Remembered as More Pleasurable? An Attempt to Test the Peak-End Rule in the Exercise Context. Issue 4 (August 2021) - Alves, Elaine Domingues; Julio, Ursula Ferreira; Panissa, Valéria Leme Gonçalves; Franchini, Emerson; Takito, Monica Yuri
Given humans' limited ability to recall past experiences for evaluation, scholars have proposed the peak-end rule stating that if perceived discomfort at the end of an aversive experience is lower than the peak discomfort experienced, the aversive experience will be remembered more positively. The purpose of this study was to evaluate the peak-end rule as applied to high-intensity interval exercise (HIIE). Participants were 30 inactive men ( M age = 27.9, SD = 5.2 years). In the first session they performed a graded exercise test on cycle-ergometer to determine their maximal aerobic power (MAP) ( M = 233, SD = 35W); and, in the second and third sessions, they performed two HIIE protocols in randomized order: (a) Short trial – 20-minutes of HIIE, composed of 30-second efforts at 100% of MAP interspersed by 30-seconds of passive recovery; and (b) Long trial – 20-minutes of the short trial, plus 10-minutes more of HIIE, decreasing 3% of MAP in each additional bout, resulting in 70% of MAP in the last bout. During exercise, we recorded the participants' rating of perceived exertion (RPE) and affect, using the Feeling Scale (FS). At 30-minutes post-exercise, we again recorded the participants' affect, using the Global Affect Evaluation (GAE) and their session-RPE, and we recorded their enjoyment, using the Physical Activity Enjoyment Scale (PACES). In the last session, the participants chose a favorite protocol to repeat. All sessions were interspersed by at least 72 hours. The 10-minutes extra HIIE in the Long-trial condition resulted decreased heart rate values ( M = 157, SD = 13bpm to M = 144, SD = 14bpm; p < 0.001), but psychological responses during and after exercise did not differ, nor did participants' preferred HIIE protocol. As the load drop for the Long-trial was not enough to change the psychological responses during exercise, there was no difference in the retrospective evaluation as the peak-end rule would have suggested.